2013
DOI: 10.3390/ijms141224338
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Reliable Reference Genes for Gene Expression Studies in the Biofuel Plant Jatropha curcas Using Real-Time Quantitative PCR

Abstract: Jatropha curcas is a promising renewable feedstock for biodiesel and bio-jet fuel production. To study gene expression in Jatropha in different tissues throughout development and under stress conditions, we examined a total of 11 typical candidate reference genes using real-time quantitative polymerase chain reaction (RT-qPCR) analysis, which is widely used for validating transcript levels in gene expression studies. The expression stability of these candidate reference genes was assessed across a total of 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…In addition, seedlings were subjected tofour different stress conditions, which included total stress,SA, PEG and NaCl. Zhang et al (2013) published a study aiming to select the best reference genes in J.curcas, using different parts of this plant under two different stress conditions: desiccation and cold treatments. Zhang et al (2013) recommended the use of reference genes GAPDH and EF1α for normalisation in qPCR assay in the reproductive stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, seedlings were subjected tofour different stress conditions, which included total stress,SA, PEG and NaCl. Zhang et al (2013) published a study aiming to select the best reference genes in J.curcas, using different parts of this plant under two different stress conditions: desiccation and cold treatments. Zhang et al (2013) recommended the use of reference genes GAPDH and EF1α for normalisation in qPCR assay in the reproductive stage.…”
Section: Discussionmentioning
confidence: 99%
“…Rocha et al (2013) were the first to identify and evaluate potential reference genes for expression studies in J. curcas for qPCR analyses, but the authors restricted their experiments to the use of developing seeds, used only six reference genes, did not include stress condition analysis, and applied only GeNorm software to normalize the data. Recently, Zhang et al (2013) published a gene expression study using reference genes in Jatropha in different tissues throughout development and only 2 under stress conditions (desiccation and cold stress treatments). The authors examined a total of 11 typical candidate reference genes using qPCR analysis, which were used for validating transcript levels in gene expression studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…LSD1 has been found to specifically catalyze the demethylation of histone 3 lysine 4 (H3K4) or histone 3 lysine 9 (H3K9) (20), and to demethylate the mono-and di-methyl groups of proteins (19). It has been shown that LSD1 suppresses gene expression by targeting histone H3K4 (21,22), while gene expression is activated by targeting histone H3K9.…”
Section: Introductionmentioning
confidence: 99%